Credibility gains from communicating with the public: Evidence from the ECB's new monetary policy strategy - Michael Ehrmann; Dimitris Georgarakos; Geoff Kenny (European Central Bank (ECB), 2023)
We show that the announcement of the ECB's Strategy Review and the revision of its inflation target in summer 2021 went largely unnoticed by the wider public. Although it is hard to reach out to this group, we find evidence that communicating key elements of the strategy can enhance the perceived credibility that price stability will be maintained in the medium-term. Randomised information treatments reveal that providing additional explanations about monetary policy's stabilising role has the strongest positive impact on credibility, boosting credibility also among the less financially literate and generating more persistent credibility gains, even after inflation increased.
Keywords: E52; E58; E31; 330; central bank communication; credibility; financial literacy; randomised controltrial; Consumer Expectations Survey